PyMR: a framework for programming magnetic resonance systems - Pizetta, Daniel Cosmo (2018)
In recent years, the use of magnetic resonance technology has grown with advances in hardware, delivering accessible and small-size equipment and devices that open a range of new applications. Innovation in this field requires versatility and flexibility of both hardware and software. Despite the technological advances in the magnetic resonance hardware, the software still the most notable problem currently. This stagnation, delays progress that could reduce production costs and deliver faster development. Researchers in this field are unsatisfied with currently available options. In this panorama, we seek the enhancement of our specific framework for programming magnetic resonance systems, employing concepts from the areas of computing, engineering, and physics. This setup allows the software to merge different perceptions, causing it to be flexible and robust. We converged to Python and object-oriented programming to offer the Python Magnetic Resonance framework - PyMR. The PyMR includes graphical interfaces from templates that can be filled with data, requiring no programming. Our framework comprises other programming tools such as our plugin for the Spyder IDE, which creates the perfect environment to create systems and the pulse sequences. Also, a user-friendly magnetic resonance simulator MR SPRINT, derived from the PyMR structure, addresses educational use, exposing the whole experiment construction, setup, and visualization. Including, PyMR has been contributing to new challenging magnetic resonance systems, introducing modern concepts to change the actual scenario the researchers are facing when developing new magnetic resonance systems.